Golden states: how California religion went from cautionary tale to global brand - Luhr, Eileen (University of California Press, 2024)
"Whether they were utopian communitarians, sun-seeking gurus, or Protestant health reformers, Southern California's spiritual seekers drew on the United States' deepening global encounters and consumer cultures to pair religious and personal reinvention with cultural and spiritual revitalization. Through a rereading of the region's cultural landscape, Golden States provides an alternative history of California religion and spirituality, showing that seekers developed a number of paths to fulfillment that enhanced the region's lifestyle brand. Drawing on case studies as varied as surfing and yoga practices, Dr. Bronner's Magic Soaps, and the only designated 'Blue Zone' in the United States, this work explores the long-term impact of alternative beliefs on the region. In doing so, it highlights the ongoing tensions between privileging personal choice and pursuing social good as communities navigated whether the commitment to the emotional and therapeutic needs and desires of individual believers should be pursued at the expense of broader efforts to achieve collective well-being"--